INOVASI MEDIA KOMBERFOSIS DAN MODEL COMPLETE STORY DI SD NEGERI 87 AMBON - Alfi Hasan (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The learning outcomes of the 4th-grade students of SDN 87 Ambon in the Islamic Religious Education is still poor, only 52% of them meet the minimum criteria of Kriteria Ketuntasan Minimal/KKM (minimum passing criteria). To minimize this weakness, learning innovations need to be carried in order to activate the students' involvement and fun literacy activities that can trigger students' interest in learning Islamic History. For this reason, the author chooses a comic as a media to study Islamic History. The comic is made from student photos using Ambon dialect language and combined with complete story learning models. Through this media or known as komberfosis (komik berbasis foto siswa), the writer records student activities by taking pictures. By using this media, the students learning outcomes increase, the average of student mastery reached 90%. Overall, the learning of Islamic Education and Budi Pekerti in the material of the Story of the Prophet's by using komberfosis media and the complete story learning model has reached KKM.